2010
DOI: 10.1103/physrevlett.105.200401
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence due to Elastic Rayleigh Scattering

Abstract: We present theoretical and experimental studies of the decoherence of hyperfine ground-state superpositions due to elastic Rayleigh scattering of light off-resonant with higher lying excited states. We demonstrate that under appropriate conditions, elastic Rayleigh scattering can be the dominant source of decoherence, contrary to previous discussions in the literature. We show that the elastic-scattering decoherence rate of a two-level system is given by the square of the difference between the elastic-scatter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
110
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 20 publications
(32 reference statements)
4
110
1
Order By: Relevance
“…While its basic properties have long been known, subtleties continue to be uncovered. Uys et al [2] have recently shown that its contribution to the decoherence rate of a ground-state superposition (two-level system) is given by the square of the difference of the scattering amplitudes; if the amplitudes interfere constructively, there is decoherence even when the rates of scattering from the two levels of the superposition are equal, contrasting previous work [3] that found such effects negligible.The elastic Rayleigh scattering considered by Uys et al is exemplified by measurements on a 9 Be + ion, with a ground-to-excited-state detuning of tens of GHz, far in excess of the excited state linewidth. In this Letter, we report on an anomalous light shift observed in a quasiresonant system of 85 Rb atoms.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…While its basic properties have long been known, subtleties continue to be uncovered. Uys et al [2] have recently shown that its contribution to the decoherence rate of a ground-state superposition (two-level system) is given by the square of the difference of the scattering amplitudes; if the amplitudes interfere constructively, there is decoherence even when the rates of scattering from the two levels of the superposition are equal, contrasting previous work [3] that found such effects negligible.The elastic Rayleigh scattering considered by Uys et al is exemplified by measurements on a 9 Be + ion, with a ground-to-excited-state detuning of tens of GHz, far in excess of the excited state linewidth. In this Letter, we report on an anomalous light shift observed in a quasiresonant system of 85 Rb atoms.…”
contrasting
confidence: 49%
“…We showed that the decoherence reported for a far-from-resonance drive in [2] evolves into an anomalous light shift (shift of opposite sign) when the scattering is quasi-resonant. The two effects are unified through their common mechanism, whereby phase is accumulated as quantum jumps map the ground state coherence when a photon is scattered.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For Raman scattering, the state is encoded in the frequency of the scattered light. For Rayleigh scattering, it is encoded in the phase of the scattered field, because the laser detuning from resonance has opposite sign for the two spin states [46]. Any atom which scatters a photon into free space therefore acquires an unknown phase, entangled with the information lost in the scattered field and uncorrelated with that of the other atoms in the ensemble.…”
Section: Effects Of Scattering Into Free Spacementioning
confidence: 99%